Enhancement of transgene expression by nuclear transcription factor Y and CCCTC‐binding factor. (9th October 2018) - Zimmerman, Devon; Patel, Krupa; Hall, Matthew; Elmer, Jacob
Abstract : If a transgene is effectively delivered to a cell, its expression may still be limited by epigenetic mechanisms that silence the transgene. Indeed, once the transgene reaches the nucleus, it may be bound by histone proteins and condensed into heterochromatin or associated with repressor proteins that block transcription. In this study, we sought to enhance transgene expression by adding binding motifs for several different epigenetic enzymes either upstream or downstream of two promoters (CMV and EF1α). Screening these plasmids revealed that luciferase expression was enhanced 10‐fold (10.4 ± 5.8) by the addition of a CCAAT box just upstream of the EF1α promoter to recruit nuclear transcription factor Y (NF‐Y), while inserting a CCCTC‐binding factor (CTCF) motif downstream of the EF1α promoter enhanced expression at least 14‐fold (14.03 ± 6.54). ChIP assays confirmed that NF‐Y and CTCF bound to the motifs that were added to each plasmid, but the presence of NF‐Y and CTCF did not significantly affect the levels of histone acetylation (H3K9ac) or methylation (H3K9me3). Overall, these results show that transgene expression from the EF1α promoter can be significantly increased with motifs that recruit NF‐Y or CTCF. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 34:1581–1588, 2018